Emerging Severe Acute Respiratory Syndrome Coronavirus 2 Mutation Hotspots Associated With Clinical Outcomes and Transmission - Pang, Xianwu; Li, Pu; Zhang, Lifeng; Que, Lusheng; Dong, Min; Xie, Bo; Wang, Qihui; Wei, Yinfeng; Xie, Xing; Li, Lanxiang; Yin, Chunyue; Wei, Liuchun; et al. (Frontiers in Microbiology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of the ongoing coronavirus disease 2019 (COVID-19) pandemic. Understanding the influence of mutations in the SARS-CoV-2 gene on clinical outcomes is critical for treatment and prevention. Here, we analyzed all high-coverage complete SARS-CoV-2 sequences from GISAID database from January 1, 2020 to January 1, 2021 to mine the mutation hotspots associated with clinical outcome and developed a model to predict the clinical outcome in different epidemic strains. Exploring the cause of mutation based on RNA-dependent RNA polymerase (RdRp) and RNA-editing enzyme. Mutation was more likely to occur in severe and mild cases than asymptomatic, especially A>G, C>T, and G>A mutation. 130 missense mutation were found associated with clinical outcome. A222V, A220V, R6997P, and V30L mutation occured together were correlated to asymptomatic outcome with high prevalence. D614G, T265I, V1176F, Q57H, R203K and G204R mutation were correlated to mild and severe outcome with high precalence. Interestingly, the SNV frequence was higher with high percentage of nt14408 mutation in RdRp in severe cases. The expression of ADAR and APOBEC was associated with clinical outcome. The model shown that the asymptomatic percentage has increased over time, while high symptomatic percentage in Alpha, Beta, and Gamma. These findings suggest that mutation in the SARS-CoV-2 genome may have a direct association with clinical outcomes and pandemic. Our result and model are helpful to predict the prevalence of epidemic strains and further study the mechanism of mutation causing severe disease.